Wear resistant all-PE single-component composites via 1D nanostructure formation during melt processing. (29th August 2018) - Hees, Timo; Zhong, Fan; Koplin, Christof; Jaeger, Raimund; Mülhaupt, Rolf
Abstract: Melt-flow-induced crystallization of polyethylene blends having tailored ultrabroad molar mass distribution affords extended-chain ultrahigh molar mass (UHMWPE) nanophases resembling nanofibers which effectively reinforce the polyethylene matrix. Unparalleled by state-of-the-art high density polyethylene (HDPE), the resulting melt-processable "all-polyethylene" single component composites exhibit simultaneously improved wear resistance, toughness, stiffness and strength. Key intermediates are trimodal blends prepared by melt compounding HDPE with bimodal UHMWPE/HDPE wax reactor blends (RB) readily tailored by ethylene polymerization on supported two-site catalysts. Whereas HDPE wax, varied up to 54 wt.-%, serves as processing aid lowering melt viscosity, UHMWPE varied up to 63 wt.-% accounts for improved blend properties. UHMWPE platelet-like nanophase separate during ethylene polymerization and readily melt during injection molding of RB/HDPE blends producing extended-chain fiber-like UHMWPE nanostructures of 100 nm diameter as shish which nucleate HDPE and HDPE wax crystallization to form shish-kebab-like structures. At 32 wt.-% UHMWPE content shish-kebab-like reinforcing phases account for massive polyethylene self-reinforcement as reflected by improved Young's modulus (+420%), tensile strength (+740%) and notched Izod impact strength (+650%) without impairing HDPE injection molding. All-PE composites exhibit high wear resistance entering ranges typical for polyamide and monomodal UHMWPE which is not processable by injection molding under identical conditions. Graphical abstract: 1D-nanostructure formation during melt processing in the presence of tunable bimodal reactor blends affords all-PE single-component composites exhibiting simultaneously improved wear resistance, stiffness, strength, and toughness. Wear resistance similar to that of UHMWPE and high performance are achieved without addition of alien materials and without sacrificing other benefits typical for HDPE commodities. Image 1 Highlights: All-PE composites containing UHMWPE contents (>30 wt.-%) are still melt processable. Mechanical performance in the range of glass-fiber reinforced polyolefins. UHMWPE/HDPE wax reactor blends can easily be used as additive and processed with HDPE. Improved wear properties are demonstrated through "ping-on ring" measurements.